LEARNING ENGLISH VOCABULARY THROUGH MOBILE-ASSISTED LANGUAGE LEARNTING (MALL): STUDENTS’ VOICES - Dwita Laksmita Rachmawati; Dian Fadhilawati (J-Shelves of Indragiri (JSI), 2025)
Vocabulary learning is a fundamental component of language mastery, as it underpins students’ ability to communicate effectively and comprehend texts. With the rapid advancement of technology, Mobile-Assisted Language Learning (MALL) has emerged as an innovative approach that enables flexible, accessible, and interactive learning experiences. However, despite its potential benefits, many university students still face challenges in expanding their English vocabulary due to limited study time, low motivation, and the lack of engaging learning resources. This study aims to explore university students’ experiences in learning English vocabulary through MALL. Employing a qualitative exploratory design, ten students from the Management Study Program at on of the private universities in Indonesia who were enrolled in an English for Specific Purposes (ESP) course participated in the research. Data were collected through semi-structured interviews and participatory observations, then analyzed using thematic analysis to identify recurring patterns and themes. The findings revealed five main themes: (1) flexibility of time and place in learning, (2) increased motivation and engagement through gamified features, (3) independent learning strategies in vocabulary acquisition, (4) technical challenges and digital distractions, and (5) the need for support from lecturers and the academic environment. Students valued the flexibility and autonomy MALL offered, as well as the motivation gained from interactive and gamified elements. Nevertheless, issues such as unstable internet connections and distractions from social media often hindered learning consistency. The study concludes that MALL enhances flexibility, motivation, and learner autonomy in vocabulary learning, yet its effectiveness depends on students’ self-discipline and institutional support. It underscores the essential role of lecturers in guiding and integrating MALL effectively into classroom instruction.